Validation of Arnaud's ethical climate index by public sector auditors in Malaysia - Loke, Chew Har; Ismail, Suhaiza; Abdul Hamid, Fatima (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this paper is to empirically test Arnaud’s (2010) ethical climate index (ECI) of measuring ethical work climate (EWC) in the context of Malaysian public sector auditors (PSAs). Design/methodology/approach – EWC is conceptualized as four main components with two subcomponents. Questionnaires were distributed to the population of PSAs in the Malaysian National Audit Department (NAD). Factor analysis (principal component analysis [PCA]) was used to verify the components of EWC. Findings – Results from PCA revealed that EWC, indeed, has four main components. Therefore, the findings of this study provide empirical evidence that validates Arnaud’s (2010) EWC model, although tested on PSAs in Malaysia. Research limitations/implications – This paper has a limited purpose, which is to test whether the ECI could be applied to PSAs in Malaysia to derive the original four main components of Arnaud’s EWC. Thus, this study does not evaluate the EWC of PSAs or determine causal relationships between EWC and other variables; these are left to future studies. Practical implications – The findings of this study confirm that Arnaud’s (2010) ECI is sufficiently resilient to be applied to the context of PSAs in Malaysia. Hence, future studies could use this index to measure EWC not only in the public sector but also in the private sector. Future research could also further test this index in different contexts. Originality/value – Arnaud’s (2010) ECI was originally applied in the context of the private sector in a developed country. Hence, this study adds value by extending the ECI to the public sector in a developing country, Malaysia.